1999
DOI: 10.1142/s0217732399002601
|View full text |Cite
|
Sign up to set email alerts
|

Father Time I: Does the Cosmic Microwave Background Radiation Provide a Universal Arrow of Time?

Abstract: in a In order to remove possible misunderstandings regarding this notation in Ref. 2, we have given a detailed operational meaning of this nonlocal GT in Appendix A. 2499 Mod. Phys. Lett. A 1999.14:2499-2505. Downloaded from www.worldscientific.com by YALE UNIVERSITY on 07/05/15. For personal use only.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A very simple experimental test for verifying this prediction has been suggested in [2], where it was also shown that the results of a balloon-borne measurement [3] of the cosmic microwave background radiation (CMBR) spectrum does seem to show such a feature a . Subject to verification of the above theoretical prediction, we argued recently [5] that, as a necessary condition for energy conservation in matter-radiation interactions, all particles in the universe subject to electromagnetic interactions should follow this one and the same arrow of time through the agency of the CMBR b . The present paper, which is a companion to [5], addresses reactions which do not conserve energy, but involve mass↔energy conversion, e.g.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…A very simple experimental test for verifying this prediction has been suggested in [2], where it was also shown that the results of a balloon-borne measurement [3] of the cosmic microwave background radiation (CMBR) spectrum does seem to show such a feature a . Subject to verification of the above theoretical prediction, we argued recently [5] that, as a necessary condition for energy conservation in matter-radiation interactions, all particles in the universe subject to electromagnetic interactions should follow this one and the same arrow of time through the agency of the CMBR b . The present paper, which is a companion to [5], addresses reactions which do not conserve energy, but involve mass↔energy conversion, e.g.…”
Section: Introductionmentioning
confidence: 85%
“…Subject to verification of the above theoretical prediction, we argued recently [5] that, as a necessary condition for energy conservation in matter-radiation interactions, all particles in the universe subject to electromagnetic interactions should follow this one and the same arrow of time through the agency of the CMBR b . The present paper, which is a companion to [5], addresses reactions which do not conserve energy, but involve mass↔energy conversion, e.g. particle-antiparticle annihilation, pair production, particle decay etc.…”
Section: Introductionmentioning
confidence: 85%